Cities, Space and Power - Osman, Amira (The Built Environment in Emerging Economies (BEinEE): Cities, Space and Transformation, 2020)
The scholarly purpose of this manuscript is to provide a resource for academics and researchers looking into cities, space and power in emerging economies. It also takes into consideration the relationship between emerging economies and developing contexts, as well as the lessons that may be shared between them. This book presents a unique perspective and aims to highlight issues not addressed much in writing on the built environment. Based on substantiation and references to numerous other sources and authors, alternative theoretical frameworks for the study of the built environment are developed. This is a very relevant contribution at this time, especially as cities will most probably go through transformations in the post-COVID-19 era. Our first line of defense against this public health crisis will be in areas of poverty, with people who have generally been excluded and urban practices that have been undocumented or labelled as informal. The main thesis of the manuscript is that space and power are strongly linked in cities. The research results prevalent in the book are original, and while the authors consult widely across disciplines, the themes are firmly rooted in the built environment fields - with a focus on the architectural discipline.